The anti-hepatic fibrosis activity of ergosterol depended on upregulation of PPARgamma in HSC-T6 cells. Issue 4 (4th April 2016) - Tai, Chen-Jei; Choong, Chen-Yen; Lin, Yu-Chun; Shi, Yeu-Ching; Tai, Cheng-Jeng
Abstract : Advanced glycation endproducts (AGEs) were shown to play an important role in metabolic syndrome and were suggested to contribute to the development of hepatic fibrosis. Abstract : Advanced glycation endproducts (AGEs) were shown to play an important role in metabolic syndrome and were suggested to contribute to the development of hepatic fibrosis. Evidence indicates that AGEs resulted in hepatic fibrosis coupled to the activation of the receptor for AGEs (RAGE) in hepatic stellate cells (HSCs). NADPH oxidase is downstream of the RAGE signaling pathway, resulting in an increase in reactive oxygen species (ROS), alpha-smooth muscle actin (alpha-SMA), RAGE, and matrix metalloproteinase-9 (MMP-9). This study was designed to evaluate the effects of ergosterol on RAGE signaling in HSC-T6 cells. Ergosterol suppressed the activation of HSC-T6 cells induced by AGEs, and attenuated overexpressions of alpha-SMA, MMP-9, and epithelial–mesenchymal transition (EMT) markers, including N-cadherin and vimentin. We also found that these inhibitory effects of ergosterol on the activation of HSCs were dependent on peroxisome proliferator-activated receptor-gamma (PPARgamma) confirmed by PPARgamma reporter assay and PPARgamma knockdown. In addition, ergosterol also showed an inhibitory effect on the generation of AGEs, fructosamine, and α-dicarbonyl compounds in this study. Our results show that ergosterol can be used as a protective agent against hepatic fibrosis caused by induction of AGEs.